Aktualisasi Isi dan Ajaran Sila-Sila dalam Pancasila untuk Meningkatkan Persatuan dan Kesatuan dalam Kehidupan Berbangsa dan Bernegara - Agnes Elsonya Damanik; Alvin Hariando Manik; Rachel Rosalina Sirait; Rhyfka Arlina Bago; Olivia Hana Putri Nababan; Ramsul Nababan (Jurnal Pendidikan dan Kewarganegara Indonesia, 2025)
This research is entitled "Actualization of the Content and Teachings of the Principles in Pancasila to Increase Unity and Oneness in National and State Life". This study aims to analyze the problems that arise in the process of actualizing Pancasila values, especially in the context of unity amidst social diversity. Identification of problems includes low public understanding of Pancasila, minimal participation in social activities, and social injustice that hinders harmony. This study uses a qualitative approach by collecting data through literature studies and interviews. The results of the study indicate that a shallow understanding of Pancasila often causes people to emphasize differences rather than similarities, thus increasing the potential for division. In addition, the rampant inaccurate information on social media worsens the situation. This study recommends the need to increase education and socialization regarding Pancasila, as well as the development of more inclusive policies to encourage active public participation. With this, it is hoped that Pancasila can be actualized as a guideline for life that strengthens the unity of the Indonesian nation, in accordance with the spirit of Bhinneka Tunggal Ika.